2010
DOI: 10.1007/s10800-010-0116-8
|View full text |Cite
|
Sign up to set email alerts
|

Time averaged calculations in pulse electrochemical machining, using a strongly non-linear model

Abstract: Simulation of the Pulse Electrochemical Machining (PECM) process can provide information on system design and guidelines for practical use. The pulses that are applied to the PECM system have to be described on a time scale that can be orders of magnitude smaller than the physical time scales in the system. If the full detail of the applied pulses has to be taken into account, the time accurate calculation of the variable distribution evolutions in PECM can become a computationally very expensive procedure. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…30 Many researchers have investigated the influence of applying pulsed potential during ECM. 5,10,11,14,15,18,19,22,23,[27][28][29][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Cook et al 31 seem to be the first group to design and apply a pulsed power supply to an ECM system. Their intention was to apply a short negative pulse after a positive pulse to remove the passive layer which was forming on the workpiece, with the aim to improve MRRs and allow machining of difficult-to-machine materials such as tungsten carbide (WC).…”
Section: Pulse Frequency and Durationmentioning
confidence: 99%
See 2 more Smart Citations
“…30 Many researchers have investigated the influence of applying pulsed potential during ECM. 5,10,11,14,15,18,19,22,23,[27][28][29][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Cook et al 31 seem to be the first group to design and apply a pulsed power supply to an ECM system. Their intention was to apply a short negative pulse after a positive pulse to remove the passive layer which was forming on the workpiece, with the aim to improve MRRs and allow machining of difficult-to-machine materials such as tungsten carbide (WC).…”
Section: Pulse Frequency and Durationmentioning
confidence: 99%
“…Meijer and Veringa 32 observed that PECM resulted in a better surface finish and tool reproduction than ECM. Van Damme et al 33 and Smets et al 35 created models of the PECM process, investigating the effects Figure 6. Model of the inter-electrode gap.…”
Section: Pulse Frequency and Durationmentioning
confidence: 99%
See 1 more Smart Citation